O canto coral sob a perspectiva da educação musical formal - Assumpção, Solange Roseli Martinelli de [UNESP] (2003)
This dissertation consists of the analysis of a specific case of the course "Canto Coral" (choral singing) included in the music course of the Arts Foundation of São Caetano do Sul, with theoretical base on authors who have written about music, education and related areas: Edgar Morin, Jean Piaget, Howard Gardner, Émile Dalcroze, Zoltán Kodály e Doreen Rao Our investigation sought out the links between the ideas of these authors which converge in the central point of our discussion - the importance of relating, in the construction of knowledge, action to understanding, the figurative to the formal, intuition to analysis Musical understanding is understood as an individual construction which each one creates through his experience and in which the human capacities of intuition and analysis connect to integrate diverse levels of understanding In face of the importance of choral singing in musical education, this study reflects on the following: on the fact that the course functions, in practice, as complementary and on pedagogic and musical ways to make it more significant in the creation musicians.